Postpartum Sterilization Choices Made by HIV-Infected Women - George D. Wendel; Donald D. McIntire; Barbara McElwee; Jeanne S. Sheffield; Paula M. Castaño; Gretchen S. Stuart (Hindawi Limited, 2005)
Objective. To assess if HIV-infected women made different choices for postpartum sterilization after implementation of the Pediatric AIDS Clinical Trials Group protocol 076 (November 1, 1994) compared to before implementation.